Norskov. Et andet Frederikshavn - Christensen, Jørgen Riber; Hansen, Kim Toft (Passage - Tidsskrift for litteratur og kritik, 2017)
Kim Toft Hansen and Jørgen Riber Christensen: “Norskov: Another Frederikshavn” In this article we examine the visual portrayal of Frederikshavn in the TV drama Norskov (2015), in which the town is more than just a provincial backdrop for the narrative. Based on production and policy studies, we illustrate the relationship between the real and the fictional town by describing the locative intentions behind the series during the production of the drama as well as the conspicuous intertextual consciousness that, perhaps surprisingly, appears not to be contrary to the creators’ interest in spatial authenticity. In conclusion, we intend to show how a portrait of a town in a fictional work, by way of basic spatial orientation, may be instrumental in the creation of a regenerated, local imagined community in a recently established Danish municipality.